Detection of Child Abuse in the Dental Office: A Literature Review - Cardona-Castañeda, Juan José (2026)
Child abuse is a global problem with physical, psychological, sexual, and social implications that seriously affect the overall development of children. In Mexico, statistics show that children and adolescents have been victims of whether physical, emotional, or sexual violence. This article aims to describe the characteristics of child abuse and mistreatment through the patient's clinical conditions for timely identification and management, as well as improve coordination as the first contact, ultimately establishing a notification protocol. A literature review was conducted on platforms such as MEDLINE, Google Scholar, and PUBMED for articles in English or Spanish published no more than 10 years ago that included samples of children and adolescents (<18 years old), with numerical data results or the estimation of the prevalence of different types of abuse, whether physical, sexual, psychological, child neglect or Munchausen syndrome, as well as the main orofacial injuries reported. A total of 35 articles were identified, of which data from 10 were included. It is noteworthy that in Mexico there is a higher prevalence of physical abuse compared to Munchausen syndrome, and a higher frequency of child sexual abuse in females. Regarding orofacial trauma, it occurs in 50% of cases of child abuse, most frequently manifesting as facial and cranial injuries and dental fractures.